Bibliometric Analysis to A Future Research Direction on Agile Transformation - Sidik Darusulistyo; Dermawan Wibisono; Harimukti Wandebori; Santi Novani (Research Synergy Foundation, 2023)
Agile transformation has become increasingly popular as a management approach to improve performance, but there has been limited research on its direction. This study aims to advance knowledge on agile transformation to help companies become faster, more flexible, and more responsive. The study employs a bibliometric approach to analyze 116